Handling of Nutmeg Post Harvest in Wawonii Timur District Konawe Kepulauan Regency - Hamrin Hamrin; La Rianda; Hermanto Hermanto (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2020)
This study aims to determine how the post-harvest handling of nutmeg in the Wawonii Timur District, Konawe Kepulaaraan Regency. The population in this study is the management of nutmeg in Wawonii Timur District, Konawe Islands Regency, with the areas of Munse Village, Munse Village, Lebo Village, Tekonea Village, Butuea Village and Wakadawu Village, and Saburano Village. Sampling was done by simple random sampling and the determination of the number of samples was purposive (intentionally) to obtain 25 attempts. Data collection was carried out through secondary data tracing, interviews, and documentation. The data were processed using descriptive and gravimetric analysis. The results of this research on the post-harvest handling of the seasonal nutmeg were 13982 kg with an average of 559.28 kg. The results of the study by using gravimetric analysis determining the water content of 8.21%, other animal dung levels of 0 Mb / lbs, no dead whole insects, no seeds with no pods, and 0.37% foreign matter. About SNI 01-0006-1993, the maximum foreign object is 0% so that it does not comply with SNI standards, while the moisture content, other animal feces, dead whole insects, and shellfish seeds are by SNI standards.